Populus trichocarpa PtNF-YA9, A Multifunctional Transcription Factor, Regulates Seed Germination, Abiotic Stress, Plant Growth and Development in Arabidopsis - Lian, Conglong; Li, Qing; Yao, Kun; Zhang, Ying; Meng, Sen; Yin, Weilun; Xia, Xinli (Frontiers in Plant Science, 2018)
NF-YAs play important roles in abiotic stress. However, their characteristics and functions in abiotic stress of poplar, a model woody plant, have not been fully investigated. Here, the biological functions of PtNF-YA9 (Potri.011G101000), an NF-YA gene from Populus trichocarpa, were first fully investigated. PtNF-YA9 is located in the nucleus. The expression of PtNF-YA9 was reduced by mannitol, NaCl, and abscisic acid (ABA). The GUS staining of ProNF-YA9::GUS transgenic lines was also reduced by mannitol treatments. In the PtNF-YA9-overexpressed Arabidopsis (OxPtNA9), OxPtNA9 lines exhibited sensitivity to simulated drought, ABA, and salinity stress during germination stage, and growth arrest emerged at post-germination stage. These phenomena might involve the ABA signaling pathway via the regulation of ABI3, ABI4, and ABI5. At vegetative stages, OxPtNA9 lines decreased in water loss via promoting stomatal closure and displayed high instantaneous water-use efficiency (WUE) of the leaf to exhibit enhanced drought tolerance. Furthermore, OxPtNA9 lines exhibited long primary root in the half-strength Murashige–Skoog agar medium supplemented with NaCl and conferred strong tolerance in the soil under salt stress. Additionally, PtNF-YA9 exhibited dwarf phenotype, short hypocotyl, small leaf area and biomass, delayed flowering, and increased chlorophyll content. Above all, our research proposes a model in which PtNF-YA9 not only plays a key role in reducing plant growth but also can play a primary role in the mechanism of an acclimatization strategy in response to adverse environmental conditions.